Doa Yesus Menurut Kallistos Ware: Transformasi Spiritual Melalui Keheningan dan Doa Yesus - Hia, Marsha; Wijaya, Hendi; Gulo, Syutriska Kardia (Paramathetes : Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract. This article explores spiritual transformation through silence and the Jesus Prayer. The Jesus Prayer, discussed in the book by Kallistos Ware, has deep origins, meaning and practice in Christian spirituality. Ware explains how Jesus' prayer was central to the prayer lives of many saints, helping to achieve union with God and a core experience with Him. Silence and the Jesus Prayer offer a space for reflection, spiritual awareness, and purification of the soul, overcoming the existential Crisis, which brings the individual closer to God. With an integration of classical spiritual theories and modern approaches, as well as personal experience, this article illustrates how the Jesus Prayer and silence complement each other in one's spiritual journey. The resulting spiritual transformation is not just a concept, but a life experience that can change deeply and provide deeper meaning for the individual who practices it. Abstrak. Artikel ini mengeksplorasi transformasi spiritual melalui keheningan dan Doa Yesus. Doa Yesus, yang dibahas dalam buku Kallistos Ware, memiliki asal usul, makna, dan praktik yang dalam dalam spiritualitas Kristen. Ware menjelaskan bagaimana doa Yesus merupakan inti kehidupan doa banyak orang kudus, membantu mencapai kesatuan dengan Tuhan dan pengalaman inti dengan-Nya. Keheningan dan Doa Yesus menawarkan ruang untuk refleksi, kesadaran spiritual, dan pemurnian jiwa, mengatasi Krisis eksistensial, yang membawa individu lebih dekat kepada Tuhan. Dengan integrasi teori spiritual klasik dan pendekatan modern, serta pengalaman pribadi, artikel ini menggambarkan bagaimana Doa Yesus dan keheningan saling melengkapi dalam perjalanan spiritual seseorang. Transformasi spiritual yang dihasilkan bukan sekedar konsep, namun merupakan pengalaman hidup yang dapat berubah secara mendalam dan memberikan makna yang lebih dalam bagi individu yang mengamalkannya.